Estimation and uncertainty analysis on carbon dioxide emissions from construction phase of real highway projects in China - Liu, Yuanyuan; Wang, Yuanqing; Li, Di (Journal of cleaner production, 2017)
Carbon dioxide emissions mitigation from road construction activities is one of potential pathways to deal with climate change. Aiming to estimate the magnitude of carbon dioxide emissions and identify the uncertainty from construction phase of real entire road projects including road structures and earthworks apart from pavement, this paper applied Life Cycle Assessment on 20 asphalt projects and 18 concrete road projects which were classified into high-grade road and low-grade road. The impact of uncertain data source and system boundary on results was checked, followed by discussion with previous studies. The findings show that average total emissions per kilometer per lane are variety but nearly 500 t for concrete and 1250 t for asphalt road. Carbon dioxide emissions comparison of asphalt road in this study with previous studies indicates that emissions of entire road project are 1.92 times higher than that of studies only considering pavement, 27% higher than that of studies without considering bridge and tunnel. Materials contribute to largest emissions in both asphalt road and concrete road, but off-road machinery even accounts for 45% of total emissions in concrete road. Emission of off-road machinery in asphalt road in this study is 13.6% higher than that of studies only considering pavement. Efforts should focus on earthworks and structures, and on improvement in off-road machinery performance not only on materials. Lack of consideration on phase of chemical reactions for cement in asphalt road and pre-consumption for fuel in concrete road could underestimate 15% of total emissions respectively. Recycling steel and electricity structure improvement play a weak role in road construction emissions reduction. For both concrete road and asphalt road, emissions of low-grade road are about 13% lower than that of high-grade road. •CO2 emissions from construction phase of real project in China based on LCA tool.•Road structures and earthworks included contribute to higher emissions.•Emissions of low-grade road are 13% lower than that of high-grade road both for concrete road and asphalt road.•Focus should be put on improvement on off-road machinery performance.•Lack of chemical reactions for cement and pre-consumption for fuel could underestimate the emissions.